Cultural Mobilities Between Africa and the Caribbean - Englert, Birgit; Gföllner, Barbara; Thomsen, Sigrid (Routledge African Diaspora Literary and Cultural Studies, 2021)
This book investigates the cultural connections between Africa and the Caribbean, using the lens of Mobility Studies to tease out the shared experiences between these highly diverse parts of the world. Despite their heterogeneity in terms of cultures, languages, and political and economic histories, the connections between the African continent and the Caribbean are manifold, stretching back to the trans-Atlantic slave trade. The authors in this book look to the past as well as to the present, focusing on the manifold mobile connections between the regions' subjects, objects, ideas, texts, images, sounds, and beliefs. In doing so, the book demonstrates that mobility extends beyond just the movement of people, and that we can also see mobility in objects and ideas, travelling either in a material sense or in imaginary terms, in physical as well as in virtual spaces. Bringing the transdisciplinary fields of African Studies, Caribbean Studies, and Mobility Studies into dialogue, this book will be of interest to students and scholars across the humanities and social sciences. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial (CC-BY-NC) 4.0 license. Funded by Universität Wien.